Development of Discovery Model-Based Learning Tool Using Cabri 3D Interactive Multimedia to Improve Students’ Mathematics Communication Ability - Julia Noviani; Nurul Qomariyah Ahmad; Julidaini Julidaini (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This study aims to develop learning tools using discovery learning models assisted by the 3D Cabri application to improve students' mathematical communication ability. This research is a development research using the 4-D Thiagarajan model which consists of 4 stages, namely define, design, develop and dissemination. The research subjects were students of SMP Negeri 5 Aceh Tengah class IX. The research instruments used were the lesson plan validation sheet, the student worksheet validation sheet, and mathematical communication ability test validation sheets, teacher response questionnaires and student response questionnaires. Data analysis techniques are validity analysis, practicality analysis and effectiveness analysis. Based on the test results, the average assessment of the three aspects of the lesson plan is 4.01 with valid criteria. The average assessment of the three aspects of the student worksheet is 4.05 with valid criteria. The average score on the three aspects of the mathematical communication test is 3.65 with valid criteria. The practicality analysis uses a teacher response questionnaire with an average practicality score of 85% and is included in the very practical category. Based on the results of the students’ response questionnaire data analysis, it was concluded that students had a positive response, namely 92.12% of the components and learning activities so that they showed effective results. The data on the effectiveness of learning outcomes were obtained from the pre-test and post-test scores of students' cognitive in learning using n-gain and the average value of the results of increasing mathematical communication ability was 0.70 which stated that mathematical communication ability increased in the medium category. The validation and testing of learning tools show that the learning tools meet the criteria for the learning tools developed, referring to being valid, practical, and effective.